Respecting a Korean health custom in a western society - Robin L. Cooper (MDPI AG, 2011)
It is a challenge to accept oddities to one’s own training and customs when in community clinics but as nurses we are trained to assess the value and impact of cultural differences in care by patients and their families. If no harm or mental discomfort will result from a séance or an ointment of religious significance applied to the forehead we go about our business and welcome patients to do as they see fit, according to their own culture and belief system. But how about if someone is applying a traditional cultural healing originating from your own culture to your own child which results in breaking the skin and results in bleeding?